Comparison of Antibody Detection between Immunoperoxidase (IIP) and Immunofluorescence (IFA) for Diagnosis of Leptospirosis - Suttirat, Sarawut; Phunpanich, Taweeporn; Rodkhunthod, Nirut; Suwannakan, Boonnipa; Muenphon, Surasak (Journal of Health Science of Thailand, 2018)
A comparison of leptospiral antibody detection between IIP and IFA was performed on samples of serum collected from 27 leptospirosis patients and 43 negative controls consisting of 10 healthy controls, 20 individuals in endemic areas and 13 non-leptospirosis. The agreement rate when two methods were compared, was 0.97 by Kappa analysis and indicated a very good agreement. Antibody titer of positive samples resulting from IIP and IFA were compared. IIP gave more titer than IFA in 16 from 28 (57.2%), equivalent titer in 9 from 28 (32.1%) and less titer than IFA in 3 from 28 (10.7%). False positive was found in two samples, one sample of VDRL and TPHA positive case and another from individual in endemic area. This preliminary study showed that IIP might be an alternative method to IFA for antibody detection. The benefit of IIP over IFA was light microscope used and its possible application for field trial study. However, more sera should be tested before its effectiveness for serodiagnosis of leptospirosis can be concluded.